Ireland : Eleventh Review Under the Extended Arrangement. (IMF Staff Country Reports; Country Report, 2013)
This paper discusses Ireland's Eleventh Review Under the Extended Arrangement. Policy implementation remains on track but recent weak GDP data point to a slower growth recovery. Real GDP declined in the first quarter, reflecting a fall in exports and weak domestic demand. Nonetheless, fiscal results remain on track and sovereign and bank bond yields have risen relatively modestly in response to declining global risk appetite. A range of other economic indicators are more encouraging, suggesting lower but still positive growth in 2013, though uncertainty remains. Growth projections for 2014 are also lowered. The IMF staff supports the authorities' request for completion of the eleventh review.